Editorial 8.3 - Lefoe, Geraldine (Journal of University Teaching and Learning Practice, 2011)
Welcome to the third and final issue of Volume 8 of the Journal of University Teaching and Learning (JUTLP) in 2011. As the year draws to a close we are seeing some striking changes to the higher education sector internationally. In England budget cuts have seen the closure of the twenty-four Higher Education Academy subject centres at the same time as the establishment of student fees. In Australia the cap has been lifted across the board on the number of students that can be enrolled in universities with the resultant projected increased student numbers. The focus in Australia is on social inclusion yet in England the concern for the introduction of fees is just the opposite, these will be the very students who may now be excluded. The changes in both countries see new measures of accountability and more complex regulations put in place. Will this cause people to rethink the way we teach and the way students learn? For the Higher Education Academy in the UK, new directions see the hosting of a summit on learning and teaching with a focus on flexible learning, an indicator of new directions for many institutions. In Australia, we see a renewed opportunity to investigate such changes through the opening of the Office of Learning and Teaching (OLT) and its role of recognising the importance of learning and teaching through grants and awards schemes. We hope in 2012 we’ll hear more from our authors about the impact of these transformations, as well as those changes occurring in other countries around the world, on teaching practice in our universities.